Patricia Williams and The Nation - Giddings, Paula J. (Columbia Journal of Gender and Law, 2014)
Patricia J. Williams has been widely admired in legal and academic circles for her role as a critical race theorist; less examined, and what I would like to talk about today, is her work as a journalist and commentator. Few are more skilled in making the tenets of a theory legible to broader audiences—or more deeply felt—than Pat.